Plant Antioxidants for Food Safety and Quality: Exploring New Trends of Research - Martina Loi; Costantino Paciolla (MDPI AG, 2021)
Antioxidants are an heterogeneous group of compounds able to counteract cell oxidation by acting as reducing agents, as free radical scavengers, and quenchers of radical species and other pro-oxidants, such as metals [...]